Autoimmune atrophic gastritis and coeliac disease: A case-control study. Issue 1 (January 2023) - Conti, Laura; Galli, Gloria; Ligato, Chiara; Carabotti, Marilia; Annibale, Bruno; Lahner, Edith
Abstract: Background: Autoimmune atrophic gastritis (AAG) is rarely associated with coeliac disease (CD). Aims: To assess the frequency of AAG-CD association and to compare clinical, biochemical, and histological features of adults affected by both diseases (cases) with AAG controls. Methods: This case-control study included 9 cases (F55%, median age 47, range 23–59yrs) matched (1:3) by age (±4 yrs) and gender to 27 controls randomly selected from our AAG cohort (2009–2021). The AAG and CD diagnosis was based on internationally agreed criteria. Results: Of 434 AAG patients (median age:62.5yrs, range18–92yrs, F:M ratio=2.2:1), 9 had a concomitant diagnosis of CD. The occurrence of AAG-CD association was 2% and 1.65% among AAG/CD cohorts, respectively. Cases were significantly younger than AAG cohort ( n  = 425, p  = 0.002). In 4/9cases, AAG was diagnosed by proactive screening for autoimmune disorders. Autoimmune thyroid disorders were present in 5/9 cases. Cases had a significant higher prevalence of normocytic anaemia than controls ( p  = 0.004). No significant differences were found between cases and controls concerning clinical and histological features. Conclusions: AAG-CD association is rare. Gastric and duodenal biopsies might be advisable in young people with normocytic anaemia and associated autoimmune disorders to timely diagnose clinically silent conditions.